Generation Z and Hajj Savings: Innovative Marketing Strategy BSI KC Palangka Raya Diponegoro - Aldina Sri Wahyuni; Qalyubi, Imam; Zulkifli (Jurnal Manajemen Bisnis, 2024)
The success of BSI KC Palangka Raya Diponegoro in attracting customers is proven by the increasing data obtained by researchers that there is a significant increase from 2022-2023 in Generation Z's interest in using Hajj savings products. BSI KC Palangka Raya Diponegoro developed a Hajj savings product with special features and marketing strategies that target the needs and preferences of Generation Z. Using a descriptive analytical approach, this research found that BSI was successful in implementing a 4P strategy which included location, product features, affordable prices and promotions. The results show that this approach is effective in increasing Generation Z's interest in Hajj savings, providing insights for better digital marketing strategies.